Sapir – Whorf Hypothesis: The Influence Of Language On Thought - Tursunova Matluba Xolmatovna (Global Scientific Publishing, 2025)
The Sapir-Whorf Hypothesis, also known as linguistic relativity, suggests that language shapes cognition and influences how individuals perceive and interpret the world. This paper examines the theoretical foundations of linguistic relativity, reviews empirical studies supporting and challenging the hypothesis, and discusses its implications in cognitive science and cross-cultural communication. Using a comparative analysis of linguistic structures and cognitive differences, this study highlights the extent to which language affects thought processes. The findings suggest that while language plays a role in shaping cognition, its influence is neither absolute nor deterministic
Keywords: hypothesis; cognition; determinism